Hubungan Pengetahuan Asupan Asupan Karbohidrat Dan Protein Pada Gizi Pekerja PT Kasiromua - Nina Isywara Kusuma; Nur Elisa (Lembaga Pengembangan Kinerja Dosen, 2022)
Background: Nutrition knowledge is knowledge about the selection of ingredients good food and daily consumption. Nutritional status is an expression of person’s nutrition in the form of certain variables, namely poor nutritional status, malnutrition, overnutrition, and obesity. Lack of knowledge about contributions nutrition from various types of food woll cause health and productivity problems in workers it is known that knowledge of nutrition provides provision for workers on how to choose healthy foods and understand that food is closely related to nutrition and health also with their productivity The quality of human resources is a major factor necessary for the successful implementation of national development. Empirical evidence indicates quality of human resources determined fromgood nutritional status, and this is determined by nutritional knowledge, the amount of food intake consumed and the physical activity of a person. Objective: The aim of this study was to analyze the relationship between nutritional knowledge, with nutritional status of workers at PT Kasiromua. Methods: The research design used was cross sectional with total of 35 subjects. Data is obtained directly and virtually through interview methods and anthropometry measurements so that the types of data used are primary and secondary data. The instruments used are microtoise, weight scales Result: Most subjects had adequate knowledge of carbohydrate and protein intake (74.3%). More than half of the subjects (57.1%) had normal nutritional status, namely 20 subjects. Conclusion: The distribution of the relationship between knowledge of carbohydrate and protein intake shows that there is a significant relationship between workers' knowledge of nutrient intake and nutritional status.